Denton Little's deathdate a novel - Rubin, Lance 1981- (Alfred A. Knopf, 2015)
"In a world where everyone knows the day they will die, a teenage boy is determined to outlive his upcoming expiration date"...
Keywords: Death; Identity; Science fiction; Identität; Science-Fiction; Tod; Todestag; Begräbnis; Denton Little; Verliebtsein; skurril; Jugendbuch